Song and significance : virtues and vices of vocal translation - Gorlée, Dinda L. (Approaches to translation studies ;, 2005)
Vocal translation is an old art, but the interpretive feeling, skill and craft have expanded into a relatively new area in translation studies. Vocal translation is the translation of the poetic discourse in the hybrid art of the musicopoetic (or poeticomusical) forms, shapes and skills. This symbiotic construct harmonizes together the conflicting roles of music and language in face-to-face singing performances. The artist sings in an accurate but free flow, but sung in a language different from the original lyrics. Vocal translation is a living-together community of composer and poet and trans.